Strategi pembelajaran jarak jauh di SMP Plus Daarul Ahgaff dalam situasi wabah pandemi COVID-19 - Sari, Dita Atika; Khamid, Abdul (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
The research aims to find out about the long-distance learning strategy during the covid-19 pandemic at junior high school plus Daarul Ahgaff. Then the supporting factors of the performance of long-distance learning, and the slowdown factors. The study involves a qualitative approach. Primary data are collected using the Google form and secondary data from related articles and literature. From the study, it is known that long-range learning strategies utilize online technology as a learning medium. The contributing factors include learning activities online, enhancing teachers' and students' ability to harness technology, and enhancing teacher and disciple creativity. And not all students have android phones, no direct interaction of teachers and students, and his fees will be internet expenses. Abstrak Tujuan dari penelitian untuk mengetahui tentang strategi pelaksanaan pembelajaran jarak jauh pada masa pandemi covid-19 di SMP Plus Daarul Ahgaff. Lalu faktor pendukung dari pelaksanaan pembelajaran jarak jauh, dan faktor penghambatnya. Penelitian ini menggunakan pendekatan kualitatif. Data primer dikumpulkan menggunakan Google form dan data sekunder dari artikel dan literatur terkait. Dari penelitian tersebut diketahui, strategi pembelajaran jarak jauh memanfaatkan teknologi daring sebagai media pembelajaran. Adapun faktor pendukung di antaranya adanya aktivitas pembelajaran secara daring, meningkatkan kemampuan para guru dan murid dalam memanfaatkan teknologi, dan meningkatkan kreativitas guru serta murid. Dan faktor penghambat tidak semuanya siswa memiliki HP android, tidak adanya interaksi langsung Guru dan murid, dan borosnya akan pengeluaran biaya internet.